A Vegetal Biopolymer-Based Biostimulant Promoted Root Growth in Melon While Triggering Brassinosteroids and Stress-Related Compounds - Lucini, Luigi; Rouphael, Youssef; Cardarelli, Mariateresa; Bonini, Paolo; Baffi, Claudio; Colla, Giuseppe (Frontiers in Plant Science, 2018)
Plant biostimulants are receiving great interest for boosting root growth during the first phenological stages of vegetable crops. The present study aimed at elucidating the morphological, physiological and metabolomic changes occurring in greenhouse melon treated with the biopolymer-based biostimulant Quik-link, containing a Root Hair Promoting Peptide (RHPP) and lignosulphonates. The vegetal-based biopolymer was applied at five rates (0, 0.06, 0.12, 0.24 or 0.48 mL plant-1) as substrate drench. The application of biopolymer-based biostimulant at 0.12 and 0.24 mL plant-1 enhanced dry weight of melon leaves and total biomass by 30.5% and 27.7%, respectively, compared to biopolymer applications at 0.06 mL plant-1 and untreated plants. The root dry biomass, total root length and surface in biostimulant-treated plants were significantly higher at 0.24 mL plant-1 and to a lesser extent at 0.12 and 0.48 mL plant-1, in comparison to 0.06 mL plant-1 and untreated melon plants. A convoluted biochemical response to the biostimulant treatment was highlighted through UHPLC/QTOF-MS metabolomics, in which brassinosteroids and their interaction with other hormones appeared to play a pivotal role. Root metabolic profile was more markedly altered than leaves, following application of the biopolymer-based biostimulant. Brassinosteroids triggered in roots could have been involved in changes of root development observed after biostimulant application. These hormones, once transported to shoots, could have caused an hormonal imbalance. Indeed, the involvement of abscisic acid, cytokinins, and gibberellin related compounds was observed in leaves following root application of the biopolymer-based biostimulant. Nonetheless, the treatment triggered an accumulation of several metabolites involved in defense mechanisms against biotic and abiotic stresses, such as flavonoids, carotenoids and glucosinolates, thus potentially improving resistance towards plant stresses.